The effects of high pressure gas burner parameters on thermal efficiency for 2014 international conference on machining, materials and mechanical technology (IC3MT) - Suttikiat Srisathit (2018)
© (2015) Trans Tech Publications, Switzerland. The KB 5 high pressure gas burners are popularly and widely used at the food stands in Thailand. The gas burner models are of various properties depending on the each factory's design. The differences of the designs affect the Liquid Petroleum Gas (LPG) consumption to a different extent. This study aimed to evaluate the parameters: the degrees of outer and inner ports; and the number of outer and inner ports of high pressure gas burners which are sold in Thailand. The thermal efficiency was tested with reference to the Standard Industrial stoves in household with liquid petroleum gas (TIS 2312-2549). The result showed that, by increasing the degrees of outer ports from 45° to 80, the thermal efficiency increased by 0.24%; while by increasing the degrees of inner ports from 50° to 60°, the thermal efficiency increased 0.11%. By increasing the number of the outer ports from 35 to 38, the thermal efficiency increased 0.44%; while by increasing the number of inner ports from 9 to 15, the thermal efficiency increased by 0.22%. The development of high pressure gas burners should focus on adjusting the degrees and number of inner and outer ports for the overall improvement of the thermal efficiency.